Microbial mechanism for enhanced methane emission in deep soil layer of Phragmites-introduced tidal marsh - Jinhyun Kim (Environment International, 2020)
The introduction of Phragmites australis is known to substantially increase methane emission in the tidal salt marsh. Previous studies suggested that enhanced carbon input by the introduction may stimulate methanogenic activity. However, the exact mechanisms and the effects of the introduction of P. australis to methane dynamics in the deep soil layer are still unclear. In this study we collected 1 m deep intact soil cores and gas samples at native Suaeda japonica- and P. australis-vegetated temperate tidal salt marshes in Suncheon Bay, Republic of Korea. Rates of methane emission and vertical distribution of soil biogeochemistry and microbial communities were analyzed to understand the relationship among chemical and microbiological properties. The introduction of P. australis significantly enhanced methane emission in sites, which was caused by increased DOC and reduced competitive inhibition between sulfate reducer and methanogens. In particular, reduced competitive inhibition between sulfate reducers and methanogens in deep soil layer may play a substantial role in the enhanced methane emission by the introduction of P. australis. Potential methane production was also significantly higher in deeper soil layers than the surface soil layer. We suggest that deep soil layer plays a critical role in the methane dynamics of tidal salt marsh which is introduced by deep root plants, such as P. australis. Keywords: Tidal salt marsh, Methane, Phragmites australis, Soil organic matter, Soil microbial community